2006
DOI: 10.1108/08858620610681623
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking market connections: mobile phone recovery, reuse and recycling in the UK

Abstract: Purpose -The purpose of this article is to provide an application of network literature that can be used for teaching and learning purposes. Design/methodology/approach -The information used to present the case study is drawn principally from documentary evidence as well as discussions with a phone manufacturer, retailer and waste management company. Findings -Describes the role of key actors in the development of "circular" supply chains for mobile phones and outlines two recovery and reuse/ recycling schemes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…The use of agent based modelling to explore the potential for creating a closed loop system for mobile phones has been reported (Bollinger et al 2011). Regardless of the take-back scheme in operation, it has been found that their effectiveness is limited by the awareness of the consumer of the need to recycle old devices (Wright et al 1998;Canning 2006;Milovantseva and Saphores 2013). et al (2014) reported the impact of mobile phones in terms of the component parts.…”
Section: Take-back Schemesmentioning
confidence: 99%
“…The use of agent based modelling to explore the potential for creating a closed loop system for mobile phones has been reported (Bollinger et al 2011). Regardless of the take-back scheme in operation, it has been found that their effectiveness is limited by the awareness of the consumer of the need to recycle old devices (Wright et al 1998;Canning 2006;Milovantseva and Saphores 2013). et al (2014) reported the impact of mobile phones in terms of the component parts.…”
Section: Take-back Schemesmentioning
confidence: 99%
“…Each year over 130 million mobile phones in the United States and over 105 million mobile phones in Europe reach their end-of-life and are thrown away (Canning, 2006). As a result used Electronic and Electrical Equipment (EEE), commonly known as e-waste, also known as WEEE (Waste Electrical and Electronic Equipment) have become a serious social problem and an environmental threat to many countries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…So, instead of preventing the thrown away to household waste by banning, events should be organized to realize the change this behavior. Mobile phones can be easily stored and forgotten or thrown away with normal household waste due to their relatively small dimensions [4,7]. Though technological developments increase WEEE amount, these advances, especially in recovery and logistics means, can be employed to reduce it.…”
Section: Challenges In Turkey and In Worldwidementioning
confidence: 99%